2019
DOI: 10.1002/arch.21609
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel homolog 1 and E93: The doorkeeper and the key to insect metamorphosis

Abstract: Insect metamorphosis is regulated by two main hormones: ecdysone (20E), which promotes molting, and juvenile hormone (JH), which inhibits adult morphogenesis. The transduction mechanisms for the respective hormonal signals include the transcription factors Krüppel homolog 1 (Kr-h1) and E93, which are JH-and 20E-dependent, respectively. Kr-h1 is the main effector of the antimetamorphic action of JH, while E93 is a key promoter of metamorphosis. The ancestral regulatory axis of metamorphosis, which operates in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 49 publications
4
44
0
Order By: Relevance
“…Moreover, these authors also showed the existence of an inverse relationship between Kr-h1 and E93 expression resulting from mutual repression effects. Our current findings therefore appear to be in agreement with the MEKRE93-based regulatory model for the control of metamorphosis (as reviewed by Belles, 2019) [ 23 ]. According to this recently proposed model, low JH titres in the final nymphal stage result in decreased signaling via Met, and this leads to reduced Kr-h1 expression, which will further result in de-repression of the E93 gene when a certain threshold is reached.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, these authors also showed the existence of an inverse relationship between Kr-h1 and E93 expression resulting from mutual repression effects. Our current findings therefore appear to be in agreement with the MEKRE93-based regulatory model for the control of metamorphosis (as reviewed by Belles, 2019) [ 23 ]. According to this recently proposed model, low JH titres in the final nymphal stage result in decreased signaling via Met, and this leads to reduced Kr-h1 expression, which will further result in de-repression of the E93 gene when a certain threshold is reached.…”
Section: Discussionsupporting
confidence: 90%
“…Significant differences in expression levels of the MEKRE93 pathway components E93 and Kr-h1 were detected in this study. Normally, the expression level of the adult specifier gene E93 increases in the second half of the final nymphal stage, when JH levels drop and ecdysteroid levels rise, to ensure the final transition to an adult [ 23 ]. Significantly downregulated SgE93 transcript levels were detected in the head of dsSgE93 -injected locusts on day four in the fifth nymphal stage, which can explain the transition to a supernumerary nymph instead of an adult locust ( Figure 3 C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A). In addition, the levels of Scg-Krh1 and Scg-E93 , situated downstream of Met in the MEKRE93 pathway in juvenile insects, were investigated as well (Belles, 2020; Belles and Santos, 2014; Lozano and Belles, 2011; Ureña et al, 2014). The significant reduction in Scg-Krh1 demonstrates that JH signaling was impaired upon silencing Scg -Met (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism that regulates insect metamorphosis is condensed in the MEKRE93 pathway (Belles and Santos, 2014), through which juvenile hormone (JH) bound to its receptor Methoprene tolerant (Met), and induces the expression of Krüppel homolog 1 (Kr-h1); this, in turn, represses the expression of E93. The players most directly involved in regulating metamorphosis are Kr-h1, the transducer of the antimetamorphic signal of JH, and E93, the master trigger of metamorphosis (see (Belles, 2019a)). E93 was originally discovered as an ecdysone-induced late prepupal specific gene, during research into the histolysis of the salivary glands in Drosophila melanogaster metamorphosis, a process in which E93 plays a key role (Baehrecke and Thummel, 1995; Lee et al, 2000; Woodard et al, 1994).…”
Section: Introductionmentioning
confidence: 99%